PENGARUH PELATIHAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA DJOURNAL COFFEE DI JAKARTA SELATAN - Siska Yunanti; Arihan Yasna (Journal of Research and Publication Innovation, 2024)
The purpose of this study was to determine the effect of training on employee performance, the effect of work discipline on employee performance and the effect of training and work discipline on employee performance at Djournal Coffee in South Jakarta. The method used in this study is descriptive with a quantitative approach, namely by describing the condition of the respondents and research variables. The population in this study were all employees of Djournal Coffee in South Jakarta. The sample used was 62 respondents with saturated sampling technique. The data analysis technique used validity test, reliability test, Classical assumption test and multiple regression through the coefficient of determination (R2), t test and f test, the result of the study is that training has a significant effect on employee performance. with a correlation coefficient value of 0.638, it means that the two variables have a strong relationship with a coefficient of determination of 63.8% with the hypotension test obtained t count > t table or (5.847 > 1.671). Work discipline has a significant effect on employee performance with a correlation coefficient of 0.693, meaning that both have a strong relationship with a coefficient of determination of 69.3% and the hypotension test obtained t count > t table or (3.205 > 1.671). Training and work discipline simultaneously have a significant effect on performance with the regression equation Y = 14,224 + 0.115X1 + 0.397X2, the coefficient of determination is 70.4%, which means that the independent and dependent variables have a strong relationship, while the remaining 29.6% is influenced by other factors. Hypotension test obtained F count > F table or (28.274 > 3.16) thus ho is rejected and Ha is accepted, thus there is a simultaneous significant effect between training and work discipline on employee performance at Djournal Coffee in South Jakarta.